Understanding the Barriers to Prisoners’ Participation in Sport Activities - Brosens, Dorien (The prison journal, 2017)
This study investigates the barriers and the predictors of these barriers that impede prisoners’ participation in sport activities. Data are derived from a project in a remand prison in Belgium (N = 486). Findings indicate that prisoners have strong preferences for other activities (e.g., work, visiting), as well as experiencing institutional barriers to sport activity. Findings show that age and time served, in particular, have an influence on the experience of the different types of barriers. Based on the research findings, the article concludes by discussing paths for further research and implications for policy and practice.